Sixth International Symposium on Quality of Electronic Design (ISQED'05)
DOI: 10.1109/isqed.2005.44
|View full text |Cite
|
Sign up to set email alerts
|

Design of High Performance Sense Amplifier Using Independent Gate Control in sub-50nm Double-Gate MOSFET

Abstract: Double-Gate (DG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Existing Circuits Fig.2 presents the Latch Based Sense Amplifier (LBSA) derived from [3]. OUTL and OUTR are being precharged to 0V before sensing.…”
Section: Sense Amplifiers For Srammentioning
confidence: 99%
“…Existing Circuits Fig.2 presents the Latch Based Sense Amplifier (LBSA) derived from [3]. OUTL and OUTR are being precharged to 0V before sensing.…”
Section: Sense Amplifiers For Srammentioning
confidence: 99%
“…The main design concerns in sense amplifiers include sensing delay, power, and tolerance to mismatch and process variations. It is shown that independent gate operation can be used to improve the design of a sense amplifier [11]. Fig.…”
Section: 2) Sense Amplifier Design In Dg Soimentioning
confidence: 99%
“…Such a short circuit prevention circuit is proposed in [11]. The short-circuit power can also be reduced by using asymmetric devices for N1 and N2, and connecting the back gates to BLB and BL.…”
Section: 2) Sense Amplifier Design In Dg Soimentioning
confidence: 99%
See 1 more Smart Citation
“…However, double gate SOI MOSFETs offer the same flexibility as PD SOI single gate MOSFETs with regard to this dynamic Vth adjustment. Moreover, it has been demonstrated that an independent control of front and back gates can be exploited to reduce both dynamic power and sensing delay in a sense amplifier design [6]. It can also be used to merge parallel transistors [7] and thus reduce dynamic power through the reduction of parasitic capacitance, as well as static power.…”
Section: Introductionmentioning
confidence: 99%